Strategic Management Accounting terhadap hubungan antara Business Strategy dan Organizational Performance saat Pandemi Covid-19 - Yohanes Mardinata Rusli (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to determine and analyze: how much the company's business strategy and strategic management accounting of a company during the COVID-19 pandemic have an influence on increasing company performance and how big the role of strategic management accounting in influencing the relationship between the company's business strategy to increase organizational performance of the company. This research has its own unique characteristics because at the time this research was conducted, the world situation was experiencing a COVID-19 pandemic in all countries of the world, including Indonesia. Data were collected using quantitative techniques from primary data sources collected from 188 questionnaires distributed to several restaurants in the Jakarta, Bandung, Surabaya and Semarang areas affiliated with publicly listed companies on the Indonesia Stock Exchange. Based on the test results from the collected questionnaires, it can be concluded that the results of this study: (1) Business Strategy has a significant influence on strategic management accounting in Indonesia; (2) The role of strategic management accounting on the relationship between Business Strategy on organizational performance in Indonesia and (3) Business Strategy has a significant influence on organizational performance in Indonesia..